TANTANGAN KEMANUSIAAN ABAD KE 21 M - Rais, M. Amien (Jurnal Bestari, 1993)
In 1970 the Rome Club cooperated with Massachussets Institute of Technology Team and Potomac Associates to publish a term paper titled